MIMO wireless power transfer based on magnetic beamforming. (2017) - Qiao, Wenhao; Wen, Zhigang
Wireless power transfer (WPT) promises to provide sufficient power for multiple users. However, majority of prior works focused on systems with single transmitter or receiver. In this paper, we base our MIMO wireless power transfer MIMO-WPT) system with N transmitters and two receivers on magnetic beamforming which is similar to that in a MIMO system of wireless communication. From the perspective of signal processing and practical application, we formulate an optimisation problem to minimise total power consumed by all transmitters, subject to the minimum power required by both receivers. Furthermore, we demonstrate that the semi-definite relaxation (SDR) of such a quadratically constrained quadratic programming (QCQP) problem is tight, thus can be solved by standard interior-point algorithm. Simulation results show that compared with the uncoordinated baseline scheme of identical current allocation, our MIMO-WPT system has boost power efficiency prominently. In the end, we consider a more general model with N transmitters and M receivers, and the characteristic of the optimal solution is deduced.